A red train : a colors book - Ford, Bernette G.; Teckentrup, Britta; Raising Readers Collection ([London] : Boxer Books Ltd. ; New York : Distributed in the U.S. and Canada by Sterling Pub. Co., 2008)
Simple text and playful collage-like illustrations link common vehicles with colors.
Title from cover.
On board pages.
Keywords: Color -- Juvenile literature; Vehicles -- Juvenile literature; Color; Vehicles; Board books